Disability studies and spanish culture : films, novels, the comic and the public exhibition (2013)
In the introduction that launches his landmark 1997 reader on the subject, Lennard J. Davis notably frames Disability Studies as a political project, embracing an approach that envisions the field as at once ‘an academic field of inquiry and an area of political inquiry’ (‘Introduction’ 1). In my view, this is yet another way of embracing the critical aim of cultural studies as described by one of the eclectic (and still forming) discipline’s founders, Raymond Williams. In 1986, Williams retrospectively summed up the premise of cultural studies as ‘the refusal to give priority to either the project or the formation—or, in older terms, the art or the society’ (152). In other words, the critic needs to grapple at once with the discourse of art (formal aspects, content, style, tone…) and also with the context in which a given work of art is produced (social, cultural, economic, political…)— while attempting to give equal weight to each. In this study, this means attending not merely to issues regarding the cultural representations of disability—which are, of course, already political—but also to research foregrounding the real-world circumstances in which disabled people find themselves as they strive to find love and engage in meaningful work. Rather than attempting an exhaustive treatment of the representation of disability in Spanish cultural products, this book is an attempt to bring a Disability Studies perspective to bear on selected Spanish materials as diverse as fiction films, documentaries, novels, and even the sequential art of the graphic novel/comic. While this book is undoubtedly a piece of humanities scholarship, it nonetheless establishes a selective dialogue with existing research on disability from a wide spectrum of approaches (philosophical, historical, social).